Consumption of alcoholic beverages during the process of Colombian independence: inspiration, celebration and conspiracy - Pico, Roger Pita (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper enquires about the inluence of the consumption of alcoholic beverages during the period of  Colombian independence. In these war days, the use ofthese beverages by troops in military camps and in the battleield was widespread, sometimes with unexpected consequences because of its excess. These beverages had a diverse use according to circumstances and intentions: to increase vigor, as a palliative, as incantation, or as a favorite ingredient for celebrating.